REVIEW: UTILIZATION OF DOMESTIC WASTE (FRUIT) AS A RAW MATERIAL SOURCE FOR THE PRODUCTION OF ECO-ENZYMES, WHICH ARE USED AS LIQUID ORGANIC FERTILIZERS AND ANTIBACTERIAL AGENTS - Bhernama, Bhayu Gita (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Domestic waste generated from households, particularly food scraps as well as vegetable and fruit residues, represents a major environmental problem when not properly managed. One alternative solution to reduce domestic waste while producing value-added products is the conversion of household organic waste into eco-enzymes. This study aimed to describe the processing of domestic waste into eco-enzymes and to evaluate their potential applications as antibacterial agents and liquid organic fertilizers. Eco-enzymes were produced through a fermentation process using domestic waste, molasses, and water at a ratio of 1:3:10 for a period of three months. The fermentation process resulted in a dark brown liquid with a characteristic acidic aroma, indicating successful microbial activity. The resulting eco-enzymes exhibited antibacterial properties and contained various macro and micro nutrients essential for plant growth, suggesting their effectiveness as disinfectants and organic liquid fertilizers. In conclusion, eco-enzymes derived from domestic waste offer a sustainable and environmentally friendly approach for waste management while providing multifunctional products with potential applications in sanitation and agriculture.